Electrochemical fabrication of porous Ni-Cu alloy nanosheets with high catalytic activity for hydrogen evolution. (10th October 2016) - Gao, M.Y.; Yang, C.; Zhang, Q.B.; Yu, Y.W.; Hua, Y.X.; Li, Y.; Dong, P.
Abstract: Porous Ni-Cu alloy films composed of nanosheets are directly fabricated on Cu substrate using a facile potentiostatic electrodeposition approach from a 1:2 choline chloride-ethylene glycol eutectic solvent (ethaline) containing nickel chloride and copper chloride. Electrochemical co-deposition of Ni-Cu alloy in ethaline is found to be thermodynamically favorable in comparison to conventional aqueous solutions. The deposition process occurs via an instantaneous nucleation and growth of nanoparticles at the initial stage and develops vertically to form nanoporous structures arrayed with nanosheets over deposition time. The as-prepared porous Ni-Cu alloy nanosheet arrays exhibit enhanced electrocatalytic activity for the hydrogen evolution reaction (HER) in alkaline media, which displays a small Tafel slope of 57.2 mV dec −1 with a low onset potential of −48 mV vs. RHE at an optimal condition. It requires small overpotentials of −128 and −150 mV to drive catalytic current densities of 10 and 20 mA cm −2, respectively. This facile electrodeposition method performed in ethaline provides an efficient way to fabricate porous Ni-based alloy nanosheets directly on a current collector, which is a promising technology for the synthesis of earth-abundant HER electrocatalysts.